Effects of Italian ryegrass with multi-enzymes supplementation on growth performance, gut microbial, and manure odor emission in finisher pig - Hong, Jun-Seon; Jeong, Yong-Dae; Park, Hyun-Ju; Choi, Yo-Han; Min, Ye-Jin; Kim, Chaehyun; Back, Soo-Hyun; Kim, Doo-Wan; Kim, Yong-Min; Kim, Jo-Eun (Journal of animal science and technology, 2024)
This study investigated the effects of addition of Italian ryegrass with multi-enzyme on growth performance, fecal odor, and microbiome. The experiment had a two-factor factorial design, using three levels of Italian ryegrass (0%, 2.5%, and 5%) and two levels of multi-enzymes (no enzyme and commercially recommended level) to formulate experimental diets. In total, 60 crossbred Landrace × Yorkshire × Duroc (LYD) pigs (88.35 ± 2.57 kg) were allocated into six dietary treatments with five replicates. After four weeks, fecal samples were collected via rectal massage for microbiome and odorous compound analysis. Results showed no significant difference ( > 0.05) in growth performance, except for feed intake ( < 0.05), which was higher in enzyme-added diets. Fecal microbiome exhibited no differences ( > 0.05) between treatments, with Firmicutes and Bacteroidetes being the major phyla, similar to the general pig population. Alpha and beta diversity analyses showed no significant differences ( > 0.05). Odorous compounds displayed no significant differences ( > 0.05), except for indoles ( < 0.05) influenced by the enzyme. In conclusion, 5% Italian ryegrass with multi-enzymes can be used as an alternative feed ingredient, having no negative effects on the growth performance, microbiome, and odorous compounds of growing pigs.